Strategic-Competitiveness for Socio-Economic Development: Unlocking the Potential of Gorontalo Province in the Context of the Nusantara Capital Integrated Development (IKN) (Jurnal Bina Praja, 2023)
The development of the Indonesian Capital City (IKN) in East Kalimantan Province was an important turning point in Indonesia's development model. Gorontalo Province as one of its close neighbors has great potential to contribute to developing IKN. Cohesion between Gorontalo Province and IKN is a key factor in achieving its socio-economic development goals. However, Gorontalo Province is still faced with problems in economic development, public services, and MSMEs, including slow local economic development, inadequate infrastructure, low community competitiveness, high levels of poverty, and socio-economic problems. This study aims to analyze the problems and potential of the Gorontalo Provincial Government in its contribution and cohesion to the socio-economic development of IKN. Through a well-being methodology (WM) approach that combines qualitative and quantitative approaches, three main dimensions are emphasized, namely perception, participation and community acceptability of competitive strategies to provide a holistic and participatory understanding of welfare aspects. The study found that the people of Gorontalo have a positive view of IKN, with the hope that the Gorontalo Provincial Government can strengthen its contribution through improving the quality of human resources, infrastructure and economic competitiveness to support the socio-economic development of IKN. Interestingly, the majority of respondents were generation Z. This shows that most of Gorontalo's young generation were involved in this research. In essence, the Gorontalo Provincial Government faces challenges in its contribution and cohesion to the socio-economic development of IKN, with low levels of public participation and a lack of public understanding of the benefits of development. Therefore, intensive efforts are needed in socialization, education, and public involvement to increase participation and strengthen the IKN development process. The Gorontalo Provincial Government is advised to design an integrated competitive strategy, focusing on increasing public perception through socialization, building trust, fostering public participation, and increasing the acceptability of IKN development.
Keywords: Competitive Strategy; Integrated Development; Socio-Economics; Nusantara Capital (IKN); Gorontalo Province